2020
DOI: 10.1155/2020/8491712
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Half-Fluence Photodynamic Therapy on Fundus Autofluorescence in Acute Central Serous Chorioretinopathy

Abstract: Purpose. To evaluate normalized short-wavelength fundus autofluorescence (SW-FAF) imaging changes over time as a predictive parameter for the retinal pigment epithelium (RPE) function in eyes compromised by acute central serous chorioretinopathy (CSCR) after indocyanine green angiography-guided verteporfin (Visudyne®, Novartis Pharma, Basel, Switzerland) photodynamic therapy (PDT) with a half-fluence rate (25 J/cm2). Methods. Quantitative data of SW-FAF grey values (SW-FAF GV) from a 350 μm (SW-350) and 1200 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Stattin et al have shown that reduced fluence PDT is an is a safe and considerable treatment option in acute CSCR. [ 9 ] Micropulse laser causes negligible thermal damage to the retina, thereby making it suitable for application in subfoveal leak. [ 10 ] For chronic CSCR, PDT has been shown to be superior to subthreshold laser in the resolution of subretinal fluid and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Stattin et al have shown that reduced fluence PDT is an is a safe and considerable treatment option in acute CSCR. [ 9 ] Micropulse laser causes negligible thermal damage to the retina, thereby making it suitable for application in subfoveal leak. [ 10 ] For chronic CSCR, PDT has been shown to be superior to subthreshold laser in the resolution of subretinal fluid and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…12 With promising results using PDT was also reported in ophthalmology. 14,15 Diabetic foot ulcers are one of the main complications in diabetic patients with high morbidity and mortality. PDT was demonstrated to reduce the microbial loads in infected diabetic ulcers without bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%